Advances in business and management forecasting. - Lawrence, Kenneth D.; Klimberg, Ronald K. (Advances in business and management forecasting ;, 2016)
Advances in Business and Management Forecasting presents state-of-the-art studies in the application of forecasting methodologies to such areas as finance, economics, technology, and forecasting accuracy. Volume 11 is split into four sections which address Forecasting in Marketing and Sales, Forecasting in Health Care, Forecasting in Business and Economics, and Topics in Forecasting. A number of topics are examined including brand experience, hospital bed management, population growth and online information sharing.